2001
DOI: 10.1002/syn.10005
|View full text |Cite
|
Sign up to set email alerts
|

Major coexpression of κ‐opioid receptors and the dopamine transporter in nucleus accumbens axonal profiles

Abstract: The behavioral effects of psychostimulants, which are produced at least in part through inhibition of the dopamine transporter (DAT), are modulated by kappa-opioid receptors (KOR) in the nucleus accumbens (Acb). Using electron microscopic immunocytochemistry, we reveal that in the Acb KOR labeling is mainly, and DAT immunoreactivity is exclusively, presynaptic. From 400 KOR-labeled presynaptic structures, including axon terminals, intervaricosities, and small axons, 51% expressed DAT and 29% contacted another … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
131
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 131 publications
(135 citation statements)
references
References 52 publications
3
131
0
1
Order By: Relevance
“…Chefer et al (2005)has suggested that dopamine release is in fact enhanced after long-term kappa blockade with NOR-BNI, but that basal dopamine concentration remains unchanged due to an increase in dopamine uptake. Thus, the KOPr system may interact with the dopamine transporter to regulate basal dopamine levels, a possibility supported by their anatomical localization (Svingos et al, 2001). How this interaction may affect dopamine dynamics during ethanol self-administration, however, is unknown at present.…”
Section: Discussionmentioning
confidence: 99%
“…Chefer et al (2005)has suggested that dopamine release is in fact enhanced after long-term kappa blockade with NOR-BNI, but that basal dopamine concentration remains unchanged due to an increase in dopamine uptake. Thus, the KOPr system may interact with the dopamine transporter to regulate basal dopamine levels, a possibility supported by their anatomical localization (Svingos et al, 2001). How this interaction may affect dopamine dynamics during ethanol self-administration, however, is unknown at present.…”
Section: Discussionmentioning
confidence: 99%
“…κ Opioid receptors are located on both the cell bodies and terminals of mosocorticolimbic DA neurons [72,73] . Activation of κ opioid receptors leads to the inhibition of DA neurons in the VTA [74] and decreases DA release in regions that receive VTA input [75,76] .…”
Section: Brain Regions Involved In κ Opioid Receptor-mediated Anxietymentioning
confidence: 99%
“…Indeed, already upon an acute injection of the kappa agonist with QNP, the depressive effects of QNP turned into locomotor excitation (Figure 2a) and the total amount of locomotion was equivalent to what could be observed after 5-6 injections of QNP alone (Figure 1). Considering that, like D2 autoreceptors, the kappa receptors regulating dopamine release are located on presynaptic dopamine terminals (Svingos et al, 2001) (as are presumably the tyrosine hydroxylase regulating kappa receptors), the coadministration of the kappa agonist probably facilitates sensitization to QNP by a presynaptic mode of action that enhances not only the blockade of dopamine release but also the reduction in basal levels of extracellular dopamine.…”
Section: A Model Of Qnp Sensitizationmentioning
confidence: 99%